2023
DOI: 10.1371/journal.pone.0281753
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and factors associated with undernutrition among children with congenital heart disease

Abstract: Background Congenital heart disease (CHD) is associated with high morbidity and mortality, especially among those with undernutrition. Evaluating risk factors associated with undernutrition is important to improve clinical outcomes. We aimed to evaluate the outcome and factors associated with undernutrition among children with CHD. Material and methods A prospective cohort study was conducted among children with CHD at Dr. Sardjito Hospital, Yogyakarta, Indonesia during February 2016 to June 2018. Clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Our study demonstrated that CHD patients with LBW were more vulnerable to FTT, which was in line with previous studies. 15 , 49 It is well recognized that neonates with CHD face an increased risk of LBW, potentially due to abnormal circulation during the fetal period. 50 Following birth, unstable hemodynamics can further impact the nutrition and oxygen supplementation until anatomical correction, which may worsen the somatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that CHD patients with LBW were more vulnerable to FTT, which was in line with previous studies. 15 , 49 It is well recognized that neonates with CHD face an increased risk of LBW, potentially due to abnormal circulation during the fetal period. 50 Following birth, unstable hemodynamics can further impact the nutrition and oxygen supplementation until anatomical correction, which may worsen the somatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired growth is linked to adverse consequences such as increased mortality, extended hospital stays, delayed cardiac surgery and postoperative complications [ 23 ]. A study reported that underweight and stunting increased mortality with an odds ratio (OR) of 3.54 and 3.31, respectively [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired growth is linked to adverse consequences such as increased mortality, extended hospital stays, delayed cardiac surgery and postoperative complications [ 23 ]. A study reported that underweight and stunting increased mortality with an odds ratio (OR) of 3.54 and 3.31, respectively [ 23 ]. Another study identified a correlation between low height-for-age and weight-for-age z-scores and post-surgery mortality in CHD patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feeding intolerance, gastric mucosal hypertrophy, and NEC were reported as associated with feeding newborns with ductal-dependent heart defects preoperatively, while receiving PGE1 treatment [ 23 , 24 ]. However, adequate nutrition is crucial for infants with congenital heart defects, as many infants are considered malnourished at the time of cardiac surgery, more so infants with cyanotic heart defects [ 25 , 26 , 27 ]. Malnutrition in these infants is multifactorial, and is due to both decreased intake, as nutritional practices have great variability between centers, and increased energy expenditure, due to their basic disease [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%